Plano de recuperação de áreas degradadas de trechos da cabeceira do Rio São Lourenço, Campo Verde – MT, mediante diagnóstico rural participativo - Checoli, Carlos Henrique Bonsi (2012)
This work had with objective recover parts of degraded permanent preservation areas; consider principles of Participatory Rural Diagnosis and the use of nucleation techniques to plant seeds. The interventions occurred on one of the tributaries that form the São Lourenço River, on county of Campo Verde, southeast of Mato Grosso. The Participatory Rural Diagnosis was adopted to strengthen the social participation, from the construction of new knowledge concerning the management of natural resources, since the study area consists of three different owners with different socio-economic profiles. There adopting participatory methodologies to stimulate the involvement of local stakeholders. The tools of participatory methodologies were used for performing joint planning, establishment of indicators, evaluation and discussion of results. Four meetings were held featuring visor UFMT development projects, starting the construction work of the collective work plan. The methodology used during the meetings was semi-structured questionnaires, Venn diagrams, matrices, transects and tables. The results of the actions were positive, enabling the extraction of information necessary for the development of the project. The execution of field work to implement the RPDA, had the full support of the owners of the areas that allowed the implementation of project activities. The concern and commitment of these was fundamental in the work field, providing the machines, employees and in some cases financial resources for the consolidation of RPDA. The total areas under reclamation of 6.5 hectares are to evaluate the development of RPDAs. Five treatment areas was choose with different recovery model: T1-natural regeneration in the area with brachiaria; T2-planting seedlings and “muvuca”, a mix of seeds, with vacuum planter and Crotalaria barrier, T3-T2 ditto without barrier;-T4 muvuca planting with vacuum planter; T5-muvuca planting with fertilizer spreader., Each treatment showed a recovery model differentiated from each other, The following progress indicators were used: Soil Cover Index (SCI) species richness, economic efficiency and comparative photographic study. The ground cover and species richness was performed by implantation of 05 treatments with 03 plots of 81 m2 each, totaling 15 plots evaluated. All treatments showed a good SCI in the great majority being over 60% of the ground cover. Species richness ranged on average from each treatment from 56.3 to 83.7 individuals planted / treatment, number of perennials ranging from 8.7 to 15 individuals per plot, and a diversity ranging from 2.7 to 5.3 perennial species/treatment. The economic analysis was performed to compare the costs for treatments for the isolation and cultivation of RPDAs, taking into account the inputs and services used in the actions, resulting in the most cost-effective treatment 02, 01 being the most treatment expensive due to the insulation around without inoculation or planting seeds and seedlings, showing just how dominant vegetation Brachiaria. Photographic study is evident in the development of areas on the ground cover and the occurrence of ecological succession and you can tell the difference between the different evolutionary stages of RPDA. As a key outcome of the work, there is the isolation of areas of RPDA, the implementation of the process of ecological restoration of riparian zones by planting muvucas seeds and seedlings, the lower costs of implementing the RPDA, resulting in improved economic and ecological efficiency in the implementation of RPDA. The project had achieved its goal and the methodologies were innovative in terms of ecological, economic and social, due to the quality of restoration ecology, economy of resources to the detriment of the conventional methods of reclamation.